SUB-ACUTE TOXICITY STUDY OF CENTELLA ASIATICA AQUEOUS EXTRACT ON THE LIVER OF RATS: DOSE-RESPONSE RELATIONSHIP ASSESSMENT - Wiyono, Tri; Nurlaila, - (Teknologi Indonesia, 2015)
Pegagan or Centella asiatica (CA) is a quite popular medicinal plant which has various properties such as anti-inflammatory and wound healing. Unfortunately, research on the toxicity of CAis still hard to find. Toxicity test of CA on spermatogenesis process had been done in previous research meanwhile its long term toxicity test has not been done. The aims of this study were to evaluate the toxicity of CA aqueous extract and to determine the relationship between the dose and toxic response when given to rats within 15 days. Forty Sprague-Dawley male rats were divided into 4 groups, then administered orally with 450, 900, 1,800 mg/kgBW of CA aqueous extract and 10 ml/kgBW distilled water as control. Observation on the liver histopathology and the levels of aspartate aminotransferase (AST) also alanine aminotransferase (ALT) in the blood indicated that there was a relationship between the dose and toxic response of CA aqueous extract on repeated administration during 15 days treatment in rats. Level of toxicity rose from congestion, steatosis, to cell necrosis. Dose of 1,800 mg/kgBW potentially led to necrosis of liver cells of rats.